Molecular fragment characteristics and distribution of tangle associated TDP-43 (TATs) and other TDP-43 lesions in Alzheimer’s disease - Josephs, Keith A.; Koga, Shunsuke; Tosakulwong, Nirubol; Weigand, Stephen D.; Pham, Nha Trang Thu; Baker, Matt; Whitwell, Jennifer L.; Rademakers, Rosa; Petrucelli, Leonard; Dickson, Dennis W. (Free Neuropathology, 2023)
TAR DNA binding protein 43 (TDP-43) pathology is a defining feature of frontotemporal lobar degeneration (FTLD). In FTLD-TDP there is a moderate-to-high burden of morphologically distinctive TDP-43 immunoreactive inclusions distributed throughout the brain. In Alzheimer’s disease (AD), similar TDP-43 immunoreactive inclusions are observed. In AD, however, there is a unique phenomenon of neurofibrillary tangle-associated TDP-43 (TATs) whereby TDP-43 intermingles with neurofibrillary tangles. Little is known about the characteristics and distribution of TATs, or how burden and distribution of TATs compares to burden and distribution of other FTLD-TDP-like lesions observed in AD. Here we characterize molecular fragment characteristics, burden and distribution of TATs and assess how these features compare to features of other TDP-43 lesions. We performed TDP-43 immunohistochemistry with anti-phosphorylated, C- and N-terminal TDP-43 antibodies in 20 high-probability AD cases and semi-quantitative burden of seven inclusion types within five brain regions (entorhinal cortex, subiculum, CA1 and dentate gyrus of hippocampus, occipitotemporal cortex). Hierarchical cluster analysis was used to analyze the dataset that consisted of 75 different combinations of neuropathological features. TATs were nonspherical with heterogeneous staining patterns and present in all regions except hippocampal dentate. All three antibodies detected TATs although N-terminal antibody sensitivity was low. Three clusters were identified: Cluster-1 had mild-moderate TATs, moderate-frequent neuronal cytoplasmic inclusions, dystrophic neurites, neuronal intranuclear inclusions and fine neurites, and perivascular and granular inclusions identified only with the N-terminal antibody throughout the brain; Cluster-2 had scant TATs in limbic regions and Cluster-3 mild-moderate TATs and mild-moderate neuronal cytoplasmic inclusions and dystrophic neurites throughout the brain and moderate fine neurites. Only 17% of cluster 1 cases had the TMEM106b GG (protective) haplotype and 83% had hippocampal sclerosis. Both features differed across clusters (p=0.03 & p=0.01). TATs have molecular characteristics, distribution and burden, and genetic and pathologic associations like FTLD-TDP lesions.